Academic modernization of the School of Public Health of Mexico: 1983-1995. - Julio Frenk; Enrique Ruelas; Octavio Gómez-Dantés; Malaquías López-Cervantes; Laura Magaña-Valladares; María Rosa Gudiño-Cejudo (Instituto Nacional de Salud Pública, 2013)
In this paper we discuss the recent efforts to modernize the School of Public Health of Mexico (ESPM). In the first part we analyze the conditions in which the ESPM operated at the beginning of the 1980s. In part two we describe the changes introduced in the ESPM between 1983 and 1986, up until its incorporation into the National Institute of Public Health (INSP). In part three we discuss the conceptual renovation which built the platform for the new academic programs introduced by the School between 1987 and 1995. In the fourth part we discuss the construction of the new facilities of INSP and the process of moving to the city of Cuernavaca. The main message of this paper is that the transformations witnessed by the ESPM in the final decades of the past century turned it into a true academic institution which uses research as the motor for training of human resources in public health.Kew words: School of Public Health of Mexico; training in public healthAutor de correspondencia: Dr. Octavio Gómez-Dantés. Genovevo de la O, 103 A, col. Santa María Ahuacatitlán. 62100 Cuernavaca, Morelos, México. Correo electrónico: ocogomez@yahoo.com